Perbaikan Desain Meja Packaging untuk AMDK Menggunakan Pengukuran Antropometri - Prima Vitasari (JASTEN (Jurnal Aplikasi Sains Teknologi Nasional), 2023)
Equipment is the most important thing in production activities as an auxiliary method when carrying out the process so that it is more effective. Bottled drinking water companies are industries whose activities use various supporting equipment in their production process. Among them is the need for appropriate packaging desk equipment. In this community service, we redesigned the bottled water packaging table. The table redesign stage includes anthropometric measurements of the employee's body. The table redesign process requires several stages such as making 2D and 3D designs and determining the tools and materials used. The size of the table is based on the calculation of the employee's posture by determining the percentile used, so that the size of the table is 88 cm high, 80 cm long and 65 cm wide using two percentiles, namely the 95th percentile for table height and 5th percentile for table length and width. By implementing a jack system on the table so that the table height is easily adjusted so that employees can easily determine the size of the table height according to their body posture.